Bilingual language acquisition : Spanish and English in the first six years - Silva-Corvalan, Carmen (Cambridge ; New York : Cambridge University Press, 2014)
'How do children develop bilingual competence? Do bilingual children develop language in the same way as monolinguals? Set in the context of findings on language development, this book examines the acquisition of English and Spanish by two brothers in the first six years of their lives. Based on in-depth and meticulous analyses of naturalistic data, it explores how the systems of both languages affect each other as the children develop, and how different levels of exposure to each language influence the nature of acquisition. The author demonstrates that the children's grammars and lexicons follow a developmental path similar to that of monolinguals, but that cross-linguistic interactions affecting lexical, semantic and discourse-pragmatic aspects arise in Spanish when exposure to it diminishes around the age of four. The first of its kind, this original study is a must-read for students and researchers in bilingualism, child development, language acquisition and language contact'--
1. Introduction; 2. Methodology; 3. Bilingual development: a linguistic profile of the first six years; 4. Subjects in English and Spanish; 5. The order of constituents: subject position in Spanish and English; 6. The acquisition of ser, estar, and be; 7. The development of verb morphology: learning how to mark tense, aspect and mood; 8. Discussion and conclusions; Appendices: 1. Transcription instructions; 2. Calculation of MLUw; 3. Spanish adjectives used with copulas up to age 6; 4. The siblings' early verb lexicon in English and Spanish; 5. Excerpt of adapted Goldilocks story.
Includes bibliographical references and index.
Keywords: Language acquisition; Bilingualism in children; Spanish language -- Acquisition; English language -- Acquisition; Grammar, Comparative and general; Bilingualism in children; English language -- Acquisition; Grammar, Comparative and general; Language acquisition; Spanish language -- Acquisition